Phylogenetic diversity of labyrinthulomycetes in Antarctic freshwater lakes - Nakai, Ryosuke; Takahashi, Yuiki; Yoshida, Masaki; Tsujimoto, Megumu; Suzuki, Atsushi C.; Kudoh, Sakae; Imura, Satoshi (2018)
The Ninth Symposium on Polar Science/Ordinary sessions: [OB] Polar biology, Wed. 5 Dec. / Entrance Hall (1st floor), National Institute of Polar Research conference object